Thermoresponsive polyurethane films for packaging applications: Effects of film formulation on their properties - Ilhan, Ilknur; Kaya, Merve; Turan, Deniz; Gunes, Gurbuz; Guner, F. Seniha; Kılıç, Ali (Elsevier BV, 2021)
Abstract Thermoresponsive films are favorable for the packaging of fresh fruits and vegetable products as their gas permeabilities increase to a greater extent than commercial films when temperature abuse occurs during refrigerated storage. Thermoresponsive polyurethane (PU) films were synthesized from polyethylene glycol (PEG) with three different molecular weights (400, 1000, and 1500 g mol−1), castor oil (CO) with two different proportions (30 and 50 %, CO/PEG ratio) and a constant level of 1,4-butanediol (BDO). The effects of these compositional factors on the thermal, mechanical, physical, structural, and gas barrier properties of the films were investigated. Melting temperatures (Tm) of the PU films varied from 25 to 29 °C and decreased with CO content. Glass transition temperatures (Tg) of the films were all below −32 °C and decreased by increased CO content. PU films with 1500 g mol−1 PEG and 30 % CO/PEG ratio had better shape memory (Rr) and shape fixity (Rf) properties than others. O2 permeabilities of the PU films were in the range of 1.99–7.25 barrer while their CO2 permeabilities were between 10.3 and 18.3 barrer. The temperature sensitivity of the gas permeabilities of the PU films was higher than that of a commercial LDPE film, which makes them more appropriate for fresh produce packaging. Nevertheless, PU films were mechanically weaker and they had higher water vapor permeability compared to the LDPE film. These properties of the PU films need further improvements for potential packaging applications.